2015
DOI: 10.1371/journal.pone.0119500
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Correlates of Emotion Regulation by Implementation Intentions

Abstract: Several studies have investigated the neural basis of effortful emotion regulation (ER) but the neural basis of automatic ER has been less comprehensively explored. The present study investigated the neural basis of automatic ER supported by ‘implementation intentions’. 40 healthy participants underwent fMRI while viewing emotion-eliciting images and used either a previously-taught effortful ER strategy, in the form of a goal intention (e.g., try to take a detached perspective), or a more automatic ER strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 100 publications
2
52
0
Order By: Relevance
“…Indeed, evidence indicates that forming if‐then plans endows responses with features of automaticity (see Gollwitzer & Sheeran, , for a review). Whereas action control by intentions operates in a ‘top‐down’, deliberative manner, neurophysiological studies indicate that if‐then plans operate in ‘bottom‐up’, cue‐driven fashion (Gilbert et al, ; Hallam et al, ), akin to the operation of habits (Gollwitzer, ; Wood & Neal, ).…”
Section: Tools For Intention Realization: Repaving the ‘Road To Hell’mentioning
confidence: 99%
“…Indeed, evidence indicates that forming if‐then plans endows responses with features of automaticity (see Gollwitzer & Sheeran, , for a review). Whereas action control by intentions operates in a ‘top‐down’, deliberative manner, neurophysiological studies indicate that if‐then plans operate in ‘bottom‐up’, cue‐driven fashion (Gilbert et al, ; Hallam et al, ), akin to the operation of habits (Gollwitzer, ; Wood & Neal, ).…”
Section: Tools For Intention Realization: Repaving the ‘Road To Hell’mentioning
confidence: 99%
“…The limbic system, including mainly the hippocampus and the amygdala nucleus, modifies our emotional reactions depending on the incoming environmental stimuli (unconscious reaction). On the other hand, the prefrontal cortex is responsible for control over emotions and feelings (realized emotions) (Table ) …”
Section: Neuroanatomical Foundation Of Ammentioning
confidence: 99%
“…Consistent with Griskevicius et al (), who proposed vigilance to relationship threats (e.g., infidelity) as an important part of their evolutionary account, we found that disillusionment events produce greater activation than did dissatisfying or regret‐inducing events in brain areas linked to self‐relevance and discrepancy monitoring. We did not find amygdala activity (presumed central to fear and avoidance; LeDoux, ) to differentiate between responses to disillusioning, dissatisfying, and regret‐inducing events, but other brain structures may have been performing a similar role (Hallam et al, ). In demonstrating the distinguishability in the brain of disillusionment from dissatisfaction and regret, our findings support unique theoretical characterizations of relationship disillusionment.…”
Section: Discussionmentioning
confidence: 77%
“…One reason could be that amygdala activation was masked by the increased activity of frontal, precuneus, and precentral regions. Hallam et al () demonstrated the role of the precuneus, frontal, and precentral gyrus in emotion regulation and amygdala activity. Our observations of these other regions suggest that participants in our study were also invested in lowering their emotional intensity when recounting disillusioning events compared to experiences when recounting dissatisfaction events.…”
Section: Discussionmentioning
confidence: 99%